The Great Wenchuan Earthquake of 2008: A Photographic Atlas of Surface Rupture and Related Disaster - Lin, Aiming; Ren, Zhikun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The magnitude Ms 8.0 (Mw 7.9) Wenchuan earthquake occurred on 12 May 2008 in the Longmen Shan region of China$1 (Bthe topographical boundary between the Tibetan Plateau and the Sichuan Basin$1 (Bresulting in extensive damage throughout central and western China. To understand the seismic faulting mechanism and surface deformation features associated with the Wenchuan earthquake, including rupture length, geometric characteristics, and slip distribution of co-seismic surface rupture, our survey group traveled to the epicentral area 2 days after the earthquake and undertook 10 days of fieldwork, during which time we collected fundamental data related to rupture structures and the spatial distribution of offset along faults. Based on the results of this preliminary fieldwork, we carried out additional detailed fieldwork along the co-seismic surface rupture over the following year. This photographic atlas shows the main deformation characteristics of co-seismic surface rupture and the nature of the earthquake disaster and subsequent relief operations, based on photographs taken during our field investigations. This atlas is intended not only for geologists, seismologists, and engineers as a means of furthering their understanding of the seismic mechanisms and surface rupture deformation characteristics of large intracontinental earthquakes, but also for advanced undergraduates and graduate students as a textbook. We are grateful to the many organizations and individuals who helped to make this book possible. Thanks are also due to Professor Dong Jia and Dr. Xiaojun Wu of the Nanjing University for their assistance in the field.s
Tectonic Setting of the Wenchuan Earthquake -- Outline of Earthquake and Focal Mechanisms -- Outline of Co-seismic Surface Rupture -- Deformation Characteristics of Co-seismic Surface Rupture -- Relationship between Surface Rupture and Pre-existing Active Faults -- Relationship between Surface Rupture and Damage to Infrastructure -- Co-seismic Landsliding and Liquefaction -- Earthquake Disaster -- Relief Operations.
Keywords: Earth sciences; Geology; Geophysics; Geotechnical engineering; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Earth Sciences; Geology; Geophysics and Environmental Physics; Geoengineering, Foundations, Hydraulics; Geotechnical Engineering & Applied Earth Sciences; Geophysics/Geodesy.; Electronic books